Emerging Moxifloxacin Resistance in Pseudomonas aeruginosa Keratitis Isolates in South India. (June 2013) - Oldenburg, Catherine E.; Lalitha, Prajna; Srinivasan, Muthiah; Rajaraman, Revathi; Ravindran, Meenakshi; Mascarenhas, Jeena; Borkar, Durga S.; Ray, Kathryn J.; Zegans, Michael E.; McLeod, Stephen D.; Porco, Travis C.; Lietman, Thomas M.; et al.
ABSTRACT Purpose: To describe temporal trends in Pseudomonas aeruginosa resistance to moxifloxacin in keratitis isolates from South India. Methods: The Steroids for Corneal Ulcers Trial (SCUT) was a randomized, double-masked, placebo-controlled trial assessing outcomes in patients with culture positive bacterial corneal ulcers randomized to receive prednisolone phosphate or placebo. All patients received moxifloxacin, and susceptibility to moxifloxacin was measured at baseline using Etest. We investigated trends in moxifloxacin susceptibility of P. aeruginosa during 2007, 2008, and 2009 isolated in SCUT in South India. Results: There were 89 P. aeruginosa isolates during 2007, 2008, and 2009 in SCUT that were eligible for this study. There was an increase in the proportion of resistant isolates from 19% in 2007 to 52% in 2009 (p = 0.02, χ2 test for trend). Logistic regression showed that there was a 2-fold increase in odds of resistance per 1 year increase during the study period (odds ratio 2.16, 95% confidence interval 1.09–4.26, p = 0.027). Conclusions: We found a sharp increase in the proportion of isolates that were resistant to moxifloxacin from 2007 to 2009. Further work needs to be done to characterize the nature of this increase.